Integrating Character Values in La Kadandio’s Poem within Linda’s Dance: A Hermeneutic Study for Cultural Education - Azahra, Wa Ode Fadhilla; Ramli, Asia; Nurwahidah, Nurwahidah (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study examines the integration of character values in the La Kadandio poem in the Linda Dance performance of the Muna community through a hermeneutic approach. As an oral literary work, La Kadandio is not merely a dance accompaniment, but rather a representation of identity, collective memory, and cultural values rooted in the historical narrative of the exile of the 11th King of Muna, La Ode Ngkadiri. This study aims to: (1) look at the structure and deeper meaning of the La Kadandio poem as a cultural text; (2) understand the character values shown in the symbols of the Linda Dance performance; (3) explain how the text, symbols, and social culture are connected using the ideas of Paul Ricoeur and Clifford Geertz; and (4) create a model to combine these values to enhance cultural education. The method used is descriptive qualitative with data collection techniques in the form of observation, in-depth interviews, documentation, and hermeneutic analysis of the poem text and performance context. The results show that the La Kadandio poem in the Linda Dance contains essential character values such as fortitude, loyalty, and local wisdom. These findings are expected to provide a comprehensive understanding of cultural symbolism and provide practical contributions to the preservation of local culture and strengthening character education based on Muna local wisdom for the younger generation.